Analisis Tentang Inovasi Program Pelayanan Kesehatan Peduli Remaja Dalam Meningkatkan Kualitas Pelayanan Publik Di Puskesmas Babakan - Mustamin Mustamin; Rahmad Hidayat; Lusiana Herawati; Mintasrihardi Mintasrihardi; M. Aprian Jaelani (Universitas Muhammadiyah Mataram, 2021)
This study was carried out at the Babakan Health Center to understand the introduction of the Youth Care Health Service innovation program and encourage and inhibit factors that enhance the quality of public services. With a sample of 40 respondents accessing services at the Babakan Health Center, the study approach used was qualitative. The method used for data collection was a questionnaire and interview. Although the data analysis approach used was qualitative analysis for interview data and quantitative percentage lines from the questionnaire. This study's findings showed that % felt happy and very satisfied with the health facilities component the implementation of the Youth Care Health Service program on the level of quality of public services. Then for the indicator of health workers hitting 57,50 % feeling happy and very satisfied. The adolescent variable hits 57,50 % feel satisfied and satisfied, network variables hit 65,00 percent feel satisfied and very satisfied, and eventually, 75,00 % feel satisfied and very satisfied with the health management variable. Overall, 65,00 % of the 5 study variables are in the satisfied and very satisfied band. Meanwhile, supporting factors include the availability of qualified workers with qualifications and competencies in their fields, the availability of air-conditioned examination room facilities, and the involvement and participation of young people in high-level activities. Moreover, the inhibiting factors include incomplete health facilities such as special counseling rooms for adolescents and inadequate room capacity, support from the community for this program is still low, and lack of cooperation in several work areas. Based on the research results, there are suggestions given that it is necessary to increase socialization to a broader extent. It is required to increase funding, especially supporting facilities and infrastructure and increasing training to existing health workers